The first Islamist republic development and disintegration of Islamism in the Sudan - Gallab, Abdullahi A. (Ashgate Pub., 2008)
By adding a new dimension to the ongoing scholarly and political debate about Islamism or political Islam within the context of modern politics in Africa, the Middle East and the Muslim world, this study details the development and disintegration of the Islamists' Republic in the Sudan.